Preliminary study of COF-based mixed matrix membranes for improved antifouling property - Nur Azizah, Johari; Noor Yahida, Yahya; Norhaniza, Yusof; Siti Nur Syazana, Zakaria (2022)
A covalent organic framework (COF) was successfully incorporated to construct a new ultrafiltration (UF) membrane via interfacial polymerization. A mixed-matrix UF membranes with concentrations COF range of 0 to 1 wt% have been prepared and characterized. The influence of COF concentration on the membrane morphology and antifouling property has been evaluated. Increasing COF concentration from 0 to 1 wt% could significantly enhance the rejection rate from 26.11% to 95.87% for bovine serum albumin (BSA). Moreover, membrane hydrophilicity significantly improved by 30.53%, with the decrease of water contact angle from 66.94° to 46.50°.